Culture of Digital Literacy in Thematic Learning at the Basic Education Level - Deffita Indah Permata Sari; Harun Joko Prayitno; Laili Etika Rahmawati; Yeni Prastiwi (Universitas Pendidikan Ganesha, 2022)
Learning during the pandemic hasn’t optimally, literacy has decreased so it is necessary to cultivate digital literacy. This study aims to analyse the cultivation of digital literacy and its supporting and inhibiting factors. This research includes qualitative research with a descriptive type. The subjects of the study were teachers, students and principals. Data collection techniques are interviews, observations, and documentation, instruments in the form of interview guidelines, observation sheets and documents. Test validity of the data using source triangulation techniques. Research data analysis is interactive analysis. The results showed that the cultivation of digital literacy can be through activities: 1) digital-based learning, 2) introduction to use of laptops, 3) education on the wise use of cellphones. The cultivation of digital literacy is influenced by several supporting factors, namely: availability of infrastructure, commitment of school residents to increase digital field, the inhibiting factors are the competence of educators, students and parents are low in the digital literacy, there isn‘t internet at home, the focus of teachers in digital literacy is lacking due many tasks, lack of infrastructure. So the cultivation of digital literacy in thematic learning in elementary schools needs to be improved in terms of infrastructure, competence of educators and students.